Mechanical Mechanism of Water Injection to Enhance the Stability of Soft Coal - Chuanqi Zhu; Hao Fan; Wanrong Liu; Shaobo Li (Advances in Materials Science and Engineering)
The physical and mechanical properties of soft coal body constitute one of the most important factors inducing coal wall spalling. In order to explore the mechanical essence of coal instability disaster and stability enhancement of water injection, the 7# coal in Huainan mining area is taken as the research object. Firstly, the distribution characteristics of coal particle size, point-load strength, original water content, microstructure characteristics, and shear strength of coal under different water contents are measured by laboratory tests. Then, based on the test results, the cementation morphology and force evolution law of granular coal water in coal body are analyzed using liquid bridge theory. The results show the following: (1) With the increase of particle size, the mass ratio of granular coal increases gradually. The percentage of particle coal with particle size less than 2.5 mm accounts for 47.157%, fractal dimension is 2.172, and uniaxial compressive strength and tensile strength are 3.822 MPa and 0.165 MPa, respectively. (2) The coal body is dry (the original moisture content is 1.336%), containing a large number of loose particles, pores, fissures, and other microfabrics. This “low water content and multiporosity” feature is the essential reason for its low strength, fragmentation, and instability and disaster. (3) In the process of water content increasing from 0.966% to 26.580%, the shear stress-displacement curve of coal body gradually changes from softening type to hardening type, and the failure type transitions from brittleness to ductility. The cohesive force increases first and then decreases, while the angle of internal friction almost has no change. (4) After reasonable water injection, the shape of liquid bridge in coal body changes into capillary tube, and the liquid bridge force reaches the maximum value, which transforms from a highly unstable bulk to a stable continuum. The research results have important theoretical significance and practical value for the safe and efficient mining of soft coal seams.